An effective dispersant for oil spills based on food-grade amphiphiles - Athas, Jasmin C (Langmuir : the ACS journal of surfaces and colloids, 2014)
Synthetic dispersants such as Corexit 9500A were used in large quantities (∼2 million gallons) to disperse the oil spilled in the ocean during the recent Deepwater Horizon event. These dispersant formulations contain a blend of surfactants in a base of organic solvent. Some concerns have been raised regarding the aquatic toxicity and environmental impact of these formulations. In an effort to create a safer dispersant, we have examined the ability of food-grade amphiphiles to disperse (emulsify) crude oil in seawater. Our studies show that an effective emulsifier is obtained by combining two such amphiphiles: lecithin (L), a phospholipid extracted from soybeans, and Tween 80 (T), a surfactant used in many food products including ice cream. Interestingly, we find that L/T blends show a synergistic effect, i.e., their combination is an effective emulsifier, but neither L or T is effective on its own. This synergy is maximized at a 60/40 weight ratio of L/T and is attributed to the following reasons: (i) L and T pack closely at the oil-water interface; (ii) L has a low tendency to desorb, which fortifies the interfacial film; and (iii) the large headgroup of T provides steric repulsions between the oil droplets and prevents their coalescence. A comparison of L/T with Corexit 9500A shows that the former leads to smaller oil droplets that remain stable to coalescence for a much longer time. The smaller size and stability of crude oil droplets are believed to be important to their dispersion and eventual microbial degradation in the ocean. Our findings suggest that L/T blends could potentially be a viable alternative for the dispersion of oil spills